When a pet dies - Rogers, Fred.; Judkis, Jim (New York : Putnam & Grosset Group, 1998)
Explores the feelings of frustration, sadness, and loneliness that a youngster may feel when a pet dies.
A PaperStar book.
Keywords: Pet owners -- Psychology -- Juvenile literature; Pets -- Death -- Psychological aspects -- Juvenile literature; Bereavement -- Psychological aspects -- Juvenile literature; Children and animals -- Juvenile literature; Children and death -- Juvenile literature; Pets -- Death; Death